A COMPARISON BETWEEN ENTERAL AND PARENTERAL METHOTREXATE INTAKE IN IRAQI PATIENTS WITH RHEUMATOID ARTHRITIS REGARDING EFFICACY AND LIVER FUNCTION IMPAIRMENT - AL-TUMA, ALI M KADHIM (Asian journal of pharmaceutical and clinical research, 2024)
Objectives: Methotrexate (MTX) is a disease-modifying ant-rheumatic drug that has been used commonly in patients with rheumatoid arthritis (RA) with a goal of reducing RA activity or RA remission. Response to MTX varied among patients and side effects including liver impairment are not uncommon. The study aimed to compare oral and parenteral MTX intake regarding the efficacy and risk of liver impairment in patients with RA. Subject: Thirty patients who were newly diagnosed with RA according to EULAR/ASAR were included in the study. MTX was given for them for 6 months in a dose ranging between 2 and 25 mg either orally or parenterally intramuscular and subcutaneously once weekly. Patients were assessed depending on clinical disease activity index (CDAI) score and liver enzymes were measured before and after the start of the treatment. Results: The study showed that parenteral MTX intake significantly improves the CDAI score more than oral intake, CDAI reduced from 13.15±3.25 to 5.57±2.34 following 6 months of treatment in comparison to its’ insignificant reduction from 12.72±3.13 to 8.90±3.08 following oral treatment. Regarding liver enzymes, the impairment in alanine aminotransferase and aspartate aminotransferase is significantly less than that with oral ones with the same effect on alkaline phosphatase. Conclusion: Parenteral MTX intake tends to be more efficacious in attaining low disease activity than oral intake with a lower rate of impaired liver function.